The relationship between mean platelet volume and dyslipidaemia in patients with metabolic syndrome and newly detected diabetes mellitus - Anar, Fouzia; Amin, Mohammod Feroz; Pathan, Md Faruque; Afsana, Faria (BIRDEM Medical Journal, 2022)
Background: High mean platelet volume (MPV) is considered as one of the most emerging cardiovascular risk factors in patients with diabetes mellitus and metabolic syndrome. The aim of this study was to find association between MPV and dyslipidaemia in both newly detected diabetes mellitus and metabolic syndrome patients. Methods: This cross-sectional study was carried out from July to December 2019, at BIRDEM General Hospital and total 115 patients were enrolled in the study. Newly detected diabetes mellitus patients (n=50) were considered in one group, whereas patients with metabolic syndrome (n=65) were in another group. Detailed history, clinical examination and biochemical parameters of the two groups were recorded. MPV was compared between the two groups and also correlated with the components of the metabolic syndrome separately. Results: Mean age of patients with metabolic syndrome and newly detected diabetes mellitus were 48.65±15.09 and 38.12±16.53 years respectively. Male were predominant in diabetic group (62%) but in metabolic syndrome group female were predominant (57%). MPV was higher in patients with metabolic syndrome (12.06±1.19 fl) than those of newly detected diabetes mellitus (10.51±1.19 fl) and this difference was statistically significant (p=0.000). Total cholesterol (213.18±82 mg/dl) and triglyceride (410.71±416.79mg/dl) in metabolic syndrome were higher than that of diabetes group (total cholesterol-156.62±49.29, triglyceride-191.10±176.18) and this was significant statistically (p=0.000, p=0.001 respectively). Positive correlation was found between MPV and total cholesterol (p=0.002) and triglyceride level (p=0 .000) in metabolic syndrome. Conclusion: Higher value of MPV was observed in patients with metabolic syndrome. Hypercholetserolaemia and hypertriglyceridaemia was also significantly associated with high MPV. BIRDEM Med J 2022; 12(3): 182-187